Al-Adatu al-Muhakkamah in The Traditional Menukur of Culture - Sudirman Suparmin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
The problem in social life is whether a custom is boeh done or not. This is certainly in line with Islamic studies which conceptualize Al-Adatu al-Muhakkamah, which is something that happens repeatedly that can be accepted by common sense and human nature which is used as a reference for law. So in this paper the author is interested in knowing the Concept of Culture in the Order of Life In Academic Studies and to know the Concept of Al-Adatu al-Muhakkamah in The Menukur of Cultural Customs. The method used in this study is a normative legal research method with an approach to cultural studies and the concept of A l-A datu al-Muhakkamah. The result of the analysis is that culture is a community habit that is carried out repeatedly which can become a habit of society. And in the concept of Al-Adatu al-Muhakkamah one of the customs that can be done must meet the elements that have been set by the scholars.